Why Multi-stakeholder Groups Succeed and Fail - Truex, Rory (2012)
Anti-corruption initiatives increasingly use multi-stakeholder groups, comprised of representatives from government, private sector, and civil society organizations, to drive implementation at the local level and serve as a force for transparency. In theory, the multi-stakeholder groups ideal is quite appealing -- each stakeholder has its own interest in the initiative and contributes its unique capacities. In practice, many multi-stakeholder groups have fallen short of expectations. This paper considers two separate but related questions. First, what are the unique barriers to implementation facing multi-stakeholder groups? Second, what policy measures can be taken to improve the likelihood that multi-stakeholder groups will succeed? The authors use existing research in political science and economics to develop a multi-level framework that accounts for the "nested nature" of multi-stakeholder groups. The framework is then applied to experiences of MSGs from the Construction Sector Transparency Initiative, a new pilot program that aims to promote transparency in construction through the release of material project information. The evidence shows that the barriers facing multi-stakeholder groups are substantial, but once the level (individual incentives, organizational dynamics, country context, or international pressures) of the challenge confronting a multi-stakeholder group is identified, the specific barrier, its root causes, and appropriate solutions can be identified. More broadly, the Construction Sector Transparency Initiative experiences suggest that multi-stakeholder groups are best used as a means of promoting dialogue and building consensus, not as the locus of policy implementation and oversight.